Cost-effective synthesis of carbazole/triphenylsilyl host materials with multiple σ-π conjugation for blue phosphorescent organic light-emitting diodes. (April 2018) - Li, Huanhuan; Tao, Ye; Chen, Runfeng; Li, Hui; Chen, Lingfeng; Jiang, Yunbo; Zheng, Chao; Huang, Wei
Abstract: Two novel multiple σ-π conjugated host materials based on both C-Si and N-Si bonding in donor-acceptor molecular architecture were designed and prepared in a highly efficient synthetic method to simultaneously introduce multiple arysilanes to carbazole in one-step and one-pot. These silicon-containing arysilanes/carbazole hybrid hosts show high thermal stability, good film-forming property, high triplet energy, suitable frontier orbital energy level, and acceptable carrier mobility due to enhanced d -orbital participation in the multiple σ-π conjugation through direct N-Si and C-Si coupling. Impressively, the multiple σ-π conjugated host materials also exhibit independently modified the electrical properties without influence the photophysical properties, rendering much improved device performance with maximum external quantum efficiency of 15.8% in blue phosphorescent organic light-emitting diodes (PhOLEDs). These findings highlight the significant importance of the multiple σ-π conjugation strategy in designing cost-effective and high-performance σ-π conjugated semiconductors for advanced optoelectronic applications. Graphical abstract: Highlights: Multiple σ-π conjugated carbazole-arylsilanes were readily synthesized in one step and one pot. Enhanced d -orbital participation through direct N-Si and C-Si coupling leads to good optoelectronic properties. High device performance with EQE over 15% was observed when used as host materials for blue PhOLEDs. Multiple σ-π conjugation strategy is effective in designing high-performance organic semiconductors for optoelectronics.